Ultrathin, Lightweight, and Flexible CNT Buckypaper Enhanced Using MXenes for Electromagnetic Interference Shielding - Yang, Rongliang; Gui, Xuchun; Yao, Li; Hu, Qingmei; Yang, Leilei; Zhang, Hao; Yao, Yongtao; Mei, Hui; Tang, Zikang (Nano-Micro Letters, 2021)
Lightweight, flexibility, and low thickness are urgent requirements for next-generation high-performance electromagnetic interference (EMI) shielding materials for catering to the demand for smart and wearable electronic devices. Although several efforts have focused on constructing porous and flexible conductive films or aerogels, few studies have achieved a balance in terms of density, thickness, flexibility, and EMI shielding effectiveness (SE). Herein, an ultrathin, lightweight, and flexible carbon nanotube (CNT) buckypaper enhanced using MXenes (Ti3C2Tx) for high-performance EMI shielding is synthesized through a facile electrophoretic deposition process. The obtained Ti3C2Tx@CNT hybrid buckypaper exhibits an outstanding EMI SE of 60.5 dB in the X-band at 100 μm. The hybrid buckypaper with an MXene content of 49.4 wt% exhibits an EMI SE of 50.4 dB in the X-band with a thickness of only 15 μm, which is 105% higher than that of pristine CNT buckypaper. Furthermore, an average specific SE value of 5.7 × 104 dB cm2 g−1 is exhibited in the 5-μm hybrid buckypaper. Thus, this assembly process proves promising for the construction of ultrathin, flexible, and high-performance EMI shielding films for application in electronic devices and wireless communications. Highlights: 1 Ultrathin, lightweight, and flexible carbon nanotube buckypaper enhanced using MXenes (Ti3C2Tx) for high-performance electromagnetic interference shielding is synthesized through facile electrophoretic deposition. 2 The obtained Ti3C2Tx@CNT hybrid buckypaper demonstrates outstanding EMI shielding effectiveness of 60.5 dB in the X-band at 100 μm and a specific SE value of 5.7 × 104 dB cm2 g−1 at 5 μm.